Philosophy of divinity Caitanya Mahāprabhu thinking and its relevance in the spirit of religious moderation - Wiguna, I Gede Pradnya (Life and Death: Journal of Eschatology, 2024)
Background: This research aims to examine in depth the philosophy of divinity in the thoughts of Caitanya  Mahāprabhu and explore its relevance in developing the spirit of religious moderation in the contemporary era. Caitanya  Mahaprabhu, a spiritual figure and philosopher from the 15th century, offered a strong philosophical foundation for overcoming polarization and promoting peaceful coexistence. Concepts such as ananya Bhakti (unconditional devotion), prema (divine love), and rasa (spiritual feeling) in Caitanya’s thought are highly relevant in building constructive interfaith dialogue and promoting mutual understanding. Method: The research method used in this research is a qualitative method. Meanwhile, the data collection method used by researchers in this research is literature study. This research uses hermeneutic theory as a theoretical basis. In the context of this research, hermeneutics is used to interpret written texts collected through literature study, with the aim of understanding the meaning contained therein. The data analysis method in this research was carried out through thematic analysis. This method allows researchers to explore the meanings contained in the data systematically and transparently. Findings: The research results show that the divine philosophy in the thoughts of Caitanya  Mahāprabhu has significant relevance to the spirit of religious moderation, especially in the current context of globalization and religious diversity. Caitanya  Mahāprabhu, with his teachings which emphasize Bhakti (devotion) and universal love, offers a framework of thought that can be used to create harmonious inter-religious dialogue and cooperation. Conclusion: The findings of this research confirm that Caitanya  Mahāprabhu’s divine philosophy offers deep and relevant insights to support the spirit of religious moderation in the modern era. Novelty/Originality in this Study: Implementing the concepts of Bhakti (unconditional devotion), prema (divine love), and humility in various aspects of social and religious life can help create a more harmonious society. So Caitanya’s philosophy has a significant contribution in building a more peaceful and civilized world, making it relevant to the spirit of religious moderation today.